Maydis leaf blight of maize: Update on status, sustainable management and genetic architecture of its resistance. (September 2022) - Kumar, Bhupender; Choudhary, Mukesh; Kumar, Krishan; Kumar, Pardeep; Kumar, Santosh; Bagaria, Pravin Kumar; Sharma, Meenakshi; Lahkar, Chayanika; Singh, Brijesh Kr; Pradhan, Hansraj; Jha, Abhishek Kumar; Kumar, Sonu; et al.
Abstract: Maize is a global principal crop, after wheat and rice. Maydis leaf blight (MLB), also known as Southern Corn Leaf Blight (SCLB), caused by Cochliobolus heterostrophus is a massive foliar disease in maize of fungal origin and prevalent in warm (20–30 °C), humid (>80%) temperate to tropical regions of the world. It has noted signification in the agricultural history due to its epidemic propositions in 1970 in the United States. At present, the primary form of C. heterostrophus is Race ′ O ′, which can cause around 40% yield losses in maize. Symptoms appear as small lesions with a dark brown margin and straw to light brown coloured center to absolute foliage blight. In spite of much availability of management practices, the use of host-plant resistance together with other integrated disease management practices may contribute effectively to the sustainable management of diseases. Both, qualitative and quantitative resistances have been reported in the literature, but quantitative is preferable over qualitative one, as it is non-race specific and highly durable. The different quantitative trait loci (QTLs) identified for MLB resistance have been mapped on chromosomes 2, 3, 4, 6, 8, and 9. Considering MLB as an important disease in India, we recommend confirming these findings and identifying new genomic regions using Indian maize germplasm as well. The progress made in the area of genomics may revolutionize the understanding of interactions between host and pathogen, and the identification and deployment of MLB resistance genes in the breeding programme. Highlights: Maydis leaf blight (MLB) is a worldwide serious foliar disease of maize that can lead to around 40% yield losses. It has noted signification in agricultural history due to its epidemic propositions in 1970 in the United States. This article contains detail on disease development, its integrated management, genetics and worldwide sources of resistance. The regions on chromosomes 2, 3, 4, 6, 8, 9 and genes viz ., ZmAPX1, ZmCCoAOMT2 and LHT1 conferred partial resistance to MLB. The resistant cultivars as components of the IDM module can contribute to the sustainable management of MLB